Influence of scCO2, Ultrasound, and Quaternary Ammonium Salt on Gelation Time and Structural Characteristics of Silica. Issue 11 (8th October 2014) - Hanu, Alina‐Mihaela; Kareth, Sabine; Puls, Angela; Ivanova, Mihaela; Mallick, Bert; Mudring, Anja‐Verena; Petermann, Marcus; Schlücker, Eberhard
Abstract In situ synthesis of silica gels via a one‐step sol‐gel process at ambient pressure or in supercritical CO2 was investigated. The influence of compressed gas, ultrasound irradiation, and quaternary ammonium salt (choline chloride) on the gelation time was determined. The obtained samples were characterized by N2 adsorption/desorption measurements, scanning electron microscopy in combination with energy dispersive X‐ray spectroscopy (SEM/EDX), and Fourier transform infrared‐attenuated total reflection spectroscopy (FTIR‐ATR). The retention capacity of the corresponding silica aerogels for Rhodamine B was evaluated as a model for organic water pollutants. The obtained results proved that scCO2 has a beneficial effect, leading to a reduction of the gelation time. The obtained aerogels exhibit a higher surface area and larger pore diameter as well as a well‐defined cylindrical pore structure.